2020
DOI: 10.1038/s41396-020-00773-1
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking microbial growth rate predictions from metagenomes

Abstract: Growth rates are central to understanding microbial interactions and community dynamics. Metagenomic growth estimators have been developed, specifically codon usage bias (CUB) for maximum growth rates and “peak-to-trough ratio” (PTR) for in situ rates. Both were originally tested with pure cultures, but natural populations are more heterogeneous, especially in individual cell histories pertinent to PTR. To test these methods, we compared predictors with observed growth rates of freshly collected marine prokary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 57 publications
2
60
1
Order By: Relevance
“…S6). This is consistent with previous work showing that CUB-based approaches can predict growth rates in low-nutrient marine microcosms (15).…”
Section: More Than One Aspect Of Codon Usage Is Associated With Growthsupporting
confidence: 93%
See 2 more Smart Citations
“…S6). This is consistent with previous work showing that CUB-based approaches can predict growth rates in low-nutrient marine microcosms (15).…”
Section: More Than One Aspect Of Codon Usage Is Associated With Growthsupporting
confidence: 93%
“…There are any number of reasons why an organism may not reproduce at its physiological maximal rate (e.g., fluctuating habitat quality, dispersal to suboptimal habitats, etc.). Nevertheless, it is encouraging that recent work using natural communities has shown that CUB-based estimators do a reasonably good job of predicting observed instantaneous growth rates in marine systems (15), even as peak to trough (77-80) methods of estimating growth have been reported to work poorly for marine plankton, with the exception of the most highly abundant copiotrophs (15). Thus, taken together with our benchmarking against nutrient enrichment experiments, the data suggest that CUB-based estimators of maximal growth rate tend to also capture the instantaneous growth rate of a community, likely by approximating the relative proportion of copiotrophs to oligotrophs in a system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting the PTR-based growth rate estimation enables using cross-sectional datasets. However, the performance of PTR-based methods is questionable ( Long et al , 2020 ), and the use of this method should be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting the PTR-based growth rate estimation enables using cross-sectional datasets. However, the performance of PTR-based methods is questionable (Long et al, 2020), and the use of this method should be considered carefully. Simulated abundance Figure 6: Simulated interaction state and bacterial abundance trajectories.…”
Section: State5mentioning
confidence: 99%